The Influence Of Liquidity, Profitability, And Asset Growth On Dividend Policy With Debt Policy As A Mediating Variable In The Banking Sector Listed On The Indonesian Stock Exchange - Sulistyawati, Anna; Hermuningsih, Sri; Hidayat, Riskin (JURNAL MANAJEMEN MOTIVASI, 2025)
This study examines the effects of liquidity, profitability, and asset growth on dividend policy, with debt policy as a mediating variable in Indonesian banking firms during the Covid-19 pandemic. Using panel data from 13 banks (2019–2023), path analysis via SEM reveals that liquidity and asset growth significantly affect debt policy, which in turn negatively impacts dividend policy. Debt policy mediates the relationship between liquidity and dividends. These findings reinforce pecking order, signaling, and agency theories in capital structure decisions amid financial uncertainty.